Effect of Composition on the Rheological Properties of (PC/ABS) and (PVDF/LDPE) Blends - Deri, F.; Hamui, M.; Al-Balaa, Imad eddin; Hamad, K.; Kaseem, M.; Nessim, Refaat I. (Journal of Applied Solution Chemistry and Modeling, 2012)
A series of blends of Acrylonitrile-Butadiene-Styrene (ABS) and Polycarbonate (PC) and another series of polyvinylidene fluoride, PVDF, and low density polyethylene, LDPE, were prepared and characterized for some of their rheological properties. The blends of a series were prepared by mixing the components, with different weight % composition, in a molten state using Brabender Plastograph. Visco-elastic parameters were measured using the capillary rheometer (Melt Index 3/80). Die-swelling rate, (B), was determined for different composition samples and correlated with the end pressure drop, (ΔPend), the end correction, (e), the apparent shear rate, (ϒa), the apparent shear stress, (τa), and the length-radius ratio, (L/R). The effects of blending composition on the die-swell rate, (B), the end correction, (e), and the shear strain, (SR) were also studied for the prepared series of blends.